IMPACT OF CODE-SWITCHING ON ENGLISH LANGUAGE PROFICIENCY AMONG SENIOR SECONDARY SCHOOL STUDENTS IN NIGERIA - Olagunju, Edijana Bose Faith; EKORO, Daniel E; GUNN, Michael (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2025)
This study examines how students in multilingual schools use code-switching when learning and working with English. Drawing on Vygotsky’s Sociocultural theory of language learning, the study surveyed 150 students joined by interviews with 10 English teachers from chosen senior secondary schools in Lagos State, Nigeria. Respondents’ views were gathered using a set of structured questionnaires for students and a standard interview of teachers. The numerical data was looked at using descriptive statistics and the interviews were interpreted through a thematic analysis. According to the findings, using code-switching in moderation while teaching helped learners understand better and take part more, but doing it too often meant they had fewer opportunities to improve their English skills. The report shows that using code-switching in a limited way can help and suggests that immersion methods should be popularized in class alongside respecting many different languages. The study finds that sometimes code-switching helps and other times not, depending on its frequency and the reason for its use. Effective promotion of English language learning depends on strategic routines in multilingual classrooms.